The assembly-activating protein promotes capsid assembly of different adeno-associated virus serotypes - Sonntag, Florian; Köther, K.; Schmidt, K.; Weghofer, M.; Raupp, C.; Nieto, K.; Kuck, A.; Gerlach, B.; Böttcher, B.; Müller, Oliver J.; Lux, K.; Hörer, M.; et al. (Journal of virology, 2011)
Adeno-associated virus type 2 (AAV2) capsid assembly requires the expression of a virally encoded assembly-activating protein (AAP). By providing AAP together with the capsid protein VP3, capsids are formed that are composed of VP3 only. Electron cryomicroscopy analysis of assembled VP3-only capsids revealed all characteristics of the wild-type AAV2 capsids. However, in contrast to capsids assembled from VP1, VP2, and VP3, the pores of VP3-only capsids were more restricted at the inside of the 5-fold symmetry axes, and globules could not be detected below the 2-fold symmetry axes. By comparing the capsid assembly of several AAV serotypes with AAP protein from AAV2 (AAP-2), we show that AAP-2 is able to efficiently stimulate capsid formation of VP3 derived from several serotypes, as demonstrated for AAV1, AAV2, AAV8, and AAV9. Capsid formation, by coexpressing AAV1-, AAV2-, or AAV5-VP3 with AAP-1, AAP-2, or AAP-5 revealed the ability of AAP-1 and AAP-2 to complement each other in AAV1 and AAV2 assembly, whereas for AAV5 assembly more specific conditions are required. Sequence alignment of predicted AAP proteins from the known AAV serotypes indicates a high degree of homology of all serotypes to AAP-2 with some divergence for AAP-4, AAP-5, AAP-11, and AAP-12. Immunolocalization of assembled capsids from different serotypes confirmed the preferred nucleolar localization of capsids, as observed for AAV2; however, AAV8 and AAV9 capsids could also be detected throughout the nucleus. Taken together, the data show that AAV capsid assembly of different AAV serotypes also requires the assistance of AAP proteins.
Gesehen am 19.10.2022